2021
DOI: 10.1016/j.celrep.2021.110079
|View full text |Cite
|
Sign up to set email alerts
|

CD19-CAR T cells undergo exhaustion DNA methylation programming in patients with acute lymphoblastic leukemia

Abstract: Highlights d CD19-CAR T cells undergo extensive DNA methylation reprogramming during therapy d DNA methylation status of the CAR T cell product can predict in vivo expansion d CD8 + CD19-CAR T cells acquire exhaustion-associated DNA methylation programs d Antigen-positive tumor relapse does not elicit CAR T cell expansion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 55 publications
(72 reference statements)
0
40
0
Order By: Relevance
“…Additionally, a subset of patients (n=6) received repeat CD19-CAR T cell infusion(s) of the same product due to recurrent malignancy or early loss of BCA. The clinical outcomes with a focus on disease response to CAR T cell therapy ( 22 , 23 ), carHLH ( 18 ), and epigenetic reprograming of CAR T cells ( 24 ), have been reported elsewhere for a subset of these patients.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a subset of patients (n=6) received repeat CD19-CAR T cell infusion(s) of the same product due to recurrent malignancy or early loss of BCA. The clinical outcomes with a focus on disease response to CAR T cell therapy ( 22 , 23 ), carHLH ( 18 ), and epigenetic reprograming of CAR T cells ( 24 ), have been reported elsewhere for a subset of these patients.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to permitting the study of primary antigen-specific Treg and Tconv responses, of importance for in vitro modeling of autoimmunity and cancer (70), our combination treatment approach also has relevant clinical implications for autologous adoptive cellular therapies (45). Studies in the delivery of chimeric antigen receptor (CAR) T cells in cancer (71, 72) and CAR Tregs in inflammatory models (73) have clearly shown that therapeutic success is reliant on dampening of memory acquisition and hindering the development of cellular exhaustion. CAR Tregs, while proposed for treatment of autoimmunity, likewise require methodological fine-tuning for prevention of exhaustion and loss of lineage stability (74).…”
Section: Discussionmentioning
confidence: 99%
“…Zebley et al . [ 209 ] performed DNA methylation profiling using serial clinical samples from patients with acute lymphoblastic leukemia (ALL) and found that post‐infusion CD8 and CD19 CAR‐T cells undergo DNA methylation reprogramming that drives cell differentiation toward exhaustion. It was also demonstrated that low‐dose DAC‐treated CD19 CAR‐T cells have stronger anti‐lymphoma, proliferation and cytokine‐releasing capacities, which is associated with less exhaustion and maintenance of memory phenotype and effector function [ 43 ].…”
Section: Advances Of Epi‐cell Therapy For Solid and Hematological Can...mentioning
confidence: 99%